Hyposialylated angiopoietin-like-4 induces apoptosis of podocytes via β1 Integrin/FAK signaling in diabetic nephropathy. (5th April 2020) - Guo, Kaifeng; Pan, Pan; Wu, Mian; Ma, Yiwen; Lu, Junxi; Chen, Haibing
Abstract: Angiopoietin-like-4 (ANGPTL4) is reported to mediate proteinuria in some types of glomerulonephropathy. However, the mechanism underlying the effect on podocytes of ANGPTL4 under pathologic conditions in diabetic nephropathy (DN) is unclear. We investigated the role of ANGPTL4 in the pathogenesis of DN. In DN rats, elevated ANGPTL4 expression was associated with increased proteinuria, glomerular hypertrophy, and ultrastructural changes in podocytes. In vitro, hyperglycemia induced the upregulation of ANGPTL4, which led to activation of integrin-β1/FAK signaling with increased apoptosis of podocytes and actin cytoskeleton derangement. These pathological changes were reversed by transfection with a lentivirus expressing short hairpin RNA against integrin-β1 or an ANGPTL4-neutralizing antibody in vitro . Furthermore, supplementation with the sialic acid precursor ManNAc reversed these pathological changes and conferred renoprotection in a mouse model of DN. Our findings suggest that ANGPTL4 mediates high glucose-induced loss of podocytes by modulating their detachment and apoptosis in vivo and in vitro . This study deepens our understanding of the mechanisms of podocyte loss in DN and shows targeting ANGPTL4-related signaling has therapeutic potential for DN. Highlights: ANGPTL4 expression is upregulated in high glucose-induced podocytes. Increased ANGPTL4 expression is associated with a hyperglycemia induced podocytes damage. ANGPTL4 induces podocytes damage via the integrinβ1/FAK pathway under high glucose. Sialic acid precursor N-acetylmannosamine (ManNAc) has renoprotective effects against DN.